Prokrastinasi Akademik Mahasantri Maâhad Al Jamiâah IAIN Kerinci - Juliawati, Dosi; Yandri, Hengki (Jurnal Fokus Konseling, 2018)
This research is motivated by the indicationÂ Mahasantri conduct academic procrastination. The purpose of this study to reveal the level of academic procrastinationÂ Mahasantri Mahad Al Jamiah IAIN Kerinci with quantitative descriptive research type with a number of research respondents as many as 102 people. Based on the results from the study revealed that the level of academic procrastination Mahasantri Mahad Al Jamiah IAIN Kerinci is in the categorys medium.Keywords: Academic Procrastination, MahasantriÂ